Perancangan Indoor Modular Meuble untuk Booth Fashion Pop-Up Market di Surabaya - Tanzil, Jackqueline; wibowo, mariana (Intra, 2016)
The scheme of indoor modular meuble as material support for pop-up market. Designer chose this topic because of the fact that pop-up market grow quickly nowadays to give online shop’s tenant a place where they can sell their product for real, consument can look the quality’s product directly, and initial capital of real shop is more expensive, so writer make design that answer the needs. A design that can be apart and be brought easily. The concepts are modular, futuristic, meuble. A meuble that give positive value to some related parties. Concept’s applications found in shape, color, and construction’s system. The purposes of this meuble-making are to know the user’s activities and give answers to the needs, best materials’ choice, good display-construction system, and making interesting booth display innovation. The data collection methods with do some observations and interviews. After that, designer starts to analyze the information and start to make the design from schematic until fix design transformation, which will be prototyped in 1:1 scale. The purposes of this meuble-making are to know the user’s activities and give the answer for the needs, choose the best materials and good display-construction system, making interesting booth display innovation